Effect of Operating Conditions on Discharge Characteristics of Petroleum Coke Powder from a Top-Discharge Blow Tank at High Pressure. Issue 5 (4th May 2017) - Guiling, Xu; Ping, Lu; Pan, Xu; Cai, Liang; Daoyin, Liu; Xiaoping, Chen
Abstract : Discharge experiments of petroleum coke powders were carried out in a pilot-scale top-discharge blow tank at high pressure. The effects of operating conditions (including fluidizing gas flow rate, blow tank pressure, differential pressure between blow tank and receiving tank, supplementary gas flow rate) on solid discharge rate and solid loading ratio were investigated. The results indicate that the maximum solid discharge rate corresponds to the most effective fluidization of the powders near the riser inlet when the fluidizing gas flow rate reaches a critical value. The solid loading ratio shows the same variation tendency as solid discharge rate with increasing fluidizing gas flow rate, which first increases then decreases. Increasing blow tank pressure can improve the fluidization of powders in the tank, which contributes to the increase of solid discharge rate; however, it would not change the basic discharge law. As the differential pressure between blow tank and receiving tank increases, the solid discharge rate increases, while the solid loading ratio first increases then decreases. Solid discharge rate and solid loading ratio both decrease as supplementary gas flow rate increases. A modified solid discharge rate prediction model is proposed for the top-discharge blow tank at high pressure with errors below ±12%.